1986
DOI: 10.1111/j.1365-2389.1986.tb00012.x
|View full text |Cite
|
Sign up to set email alerts
|

Microaggregates in red earths and related soils in East and Central Africa, their classification and occurrence

Abstract: This paper describes the microaggregate structure of residual clay soils of the red earth order in East and Central Africa, examined by low-power microscopy, and the effects of gradual moistening and sudden wetting of the soil. Results showed a markedly angular microstructure termed fragmental, resulting from simple cleavages in the soil mass, a microgranular structure involving minute spherical bodies, either discrete or in small compound aggregates, and two types of intermediate structure. The several types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
8

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 6 publications
2
18
0
8
Order By: Relevance
“…The result of this intense fissuration of the porphyric groundmass is the creation of a network of planar voids isolating polyedric microaggregates (PM) that are later included into the enaulic soil matrix by pedoturbation processes. Trapnell & Webster (1986) observed the same process of microaggregate formation, calling them fragmental aggregates.…”
Section: Origin Of the Microaggregate Structurementioning
confidence: 85%
See 1 more Smart Citation
“…The result of this intense fissuration of the porphyric groundmass is the creation of a network of planar voids isolating polyedric microaggregates (PM) that are later included into the enaulic soil matrix by pedoturbation processes. Trapnell & Webster (1986) observed the same process of microaggregate formation, calling them fragmental aggregates.…”
Section: Origin Of the Microaggregate Structurementioning
confidence: 85%
“…Consequently, the formation of the microaggregate structure can be considered complex due to the existence of various hypotheses that may explain their formation and shape. Among them, a biological origin of microaggregates (Stoops, 1983;Eschenbrenner, 1986;Miklós, 1992;Vidal-Torrado, 1994), a geochemical origin (Chauvel et al, 1978;Cambier, 1986;Pedro, 1987;Santos et al, 1989) and finally a physical origin by fragmentation (Muller, 1977;Trapnell & Webster, 1986) may be involved.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of such layers in soils is thought to be due to the transport by termites of fme materials to the surface for mound and surface sheeting construction. Recent studies using micromorphological techniques have also concluded that the relic features of many tropical soils are a result of both pronounced leaching over extended periods of time, and continuous disturbance and homogenization, principally through termite activity [92,96,99]. Examination of microaggregate structure in such soils has revealed termite derived aggregates and lends further support for this hypothesis [23,92,99,100].…”
Section: Soil Translocationmentioning
confidence: 87%
“…Microaggregates are near spherical ranging from 80 to 300 μm in size usually. They correspond to the 'pseudosand', 'micropeds', 'granules' described earlier by Kubiena (1950), Brewer (1964) and Trapnell and Webster (1986), respectively. Thus, Ferralsols porosity is closely related to the arrangement of microaggregates and the packing of clay particles within the microaggregates with a contribution of large pores resulting from biological activity.…”
Section: Introductionmentioning
confidence: 99%